2021
DOI: 10.3390/pathogens10010029
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilin-Producing Strains of Haemophilus haemolyticus Protect Respiratory Epithelia from NTHi Colonisation and Internalisation

Abstract: Nontypeable Haemophilus influenzae (NTHi) is a significant respiratory tract pathogen responsible for infections that collectively pose a substantial health and socioeconomic burden. The clinical course of these infections is largely dictated by NTHi interactions with host respiratory epithelia, and thus, approaches that disrupt colonisation and invasion may have significant therapeutic potential. Survival, successful host–cell interactions, and pathogenesis are reliant on NTHi’s ability to sequester host-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Production of the Hpl haemophore has previously been shown to mediate the in vitro inhibitory capacity of Hh against NTHi growth and the adherence/invasion of model respiratory cell lines by restricting NTHi access to the essential nutrient haem [ 22 , 23 , 24 ]. Although we postulate that the same mechanism may be involved here, the study design reports on the presence of the hpl coding region and does not assess phenotypic production of the Hpl protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of the Hpl haemophore has previously been shown to mediate the in vitro inhibitory capacity of Hh against NTHi growth and the adherence/invasion of model respiratory cell lines by restricting NTHi access to the essential nutrient haem [ 22 , 23 , 24 ]. Although we postulate that the same mechanism may be involved here, the study design reports on the presence of the hpl coding region and does not assess phenotypic production of the Hpl protein.…”
Section: Resultsmentioning
confidence: 99%
“…Although we postulate that the same mechanism may be involved here, the study design reports on the presence of the hpl coding region and does not assess phenotypic production of the Hpl protein. We have previously shown that even among Hh strains containing identical hpl ORF sequences, some strains lack the capacity to express hpl and produce the Hpl protein that mediates NTHi inhibitory activity in vitro [ 23 , 24 , 44 ]. However, the majority (16/17) of Hh- hpl + detectable by our PCR assay from our culture collection produce Hpl and elicit NTHi-inhibitory activity ( Table S4 ), and there are no incidences of Hpl production in strains that do not contain the hpl ORF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H. parahaemolyticus strains possess Tf receptors whereas only some strains of H. haemolyticus do. However, the demonstrated competition between H. haemolyticus and H. influenzae (Atto et al, 2021) and similarity in adhesins (Singh et al, 2013) suggests that at least some strains of H. haemolyticus occupy the same niche. All strains of Glaesserella parasuis possess Tf receptors, with more virulent serovars possessing genes involved in binding to the mucosal surface.…”
Section: Development Of Infection Modelsmentioning
confidence: 99%
“…In the absence of Hpl, H. haemolyticus growth is impaired without an alternative source of heme such as hemoglobin, which can be imported by other mechanisms ( 17 ). Importantly, Hpl binds heme in a manner that cannot be utilized by NTHi, thus inhibiting NTHi growth in vitro ( 17 20 ). In humans, colonization with Hpl-expressing H. haemolyticus is associated with lower NTHi burdens in the upper airway and a reduced risk of NTHi acquisition, suggesting a beneficial role for Hpl expression ( 21 ).…”
Section: Introductionmentioning
confidence: 99%